2023
DOI: 10.7759/cureus.35260
|View full text |Cite
|
Sign up to set email alerts
|

Challenge Accepted: Retinopathy of Prematurity (ROP) During COVID-19

Abstract: The World Health Organization has identified retinopathy of prematurity (ROP) as one of the emerging causes of preventable childhood blindness in developing and middle-income countries. It is becoming a major public health problem in developing countries like India and China. ROP blindness in India is increasing due to the highest number of preterm births in the world, suboptimal neonatal care, lack of awareness, screening programs and treatment not in place, and increasing numbers of neonatal intensive care u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Routine health services were often curtailed during lockdown, including surgery for congenital conditions. (8, 9) We identi ed six studies on the impact on ROP services, from the USA,( 10) India (11,12,13,14) and China. (15) Two described the mitigation measures adopted which allowed services to continue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine health services were often curtailed during lockdown, including surgery for congenital conditions. (8, 9) We identi ed six studies on the impact on ROP services, from the USA,( 10) India (11,12,13,14) and China. (15) Two described the mitigation measures adopted which allowed services to continue.…”
Section: Discussionmentioning
confidence: 99%
“…(15) Two described the mitigation measures adopted which allowed services to continue. (10,14) The other studies all report that fewer infants were screened during lockdown, with a variable impact on the number treated. This may re ect publication bias, as half of the eSurvey participants in our study reported no or only minimal impact on screening or treatment.…”
Section: Discussionmentioning
confidence: 99%